Factor that contribute to conflict at Perbendaharaan Negeri Selangor / Siti Nadhirah Thanaiem Mohd Naziruddin and Dewi Nor Farihah Radin Nor Azam - Mohd Naziruddin, Siti Nadhirah Thanaiem; Radin Nor Azam, Dewi Nor Farihah (Faculty of Administrative Science and Policy Studies, 2014)
The conflict in organizational now a comment issues face by organizational. Organizations are regularly worried about issues of conflict that involve in the department. The main objective of this research are to indentified the most influential factor that contributes to the organizational conflict either emotional (relationship) or constructive (task related) . The scope in this research are Perbendaharaan Negeri Selangor. The secondary data collected from different sources such as journal, internet, books, and articles.